"Race" versus "ethnicity"? Critical race essentialism and the exclusion and oppression of migrants in the Netherlands. Issue 3 (19th February 2017) - Siebers, Hans
ABSTRACT: Howard Winant subordinates "ethnicity" to "race" as the central structuring principle in society. By contrast, Andreas Wimmer takes racism as a particular form of ethnic boundary making. Their debate in this journal (vol. 38, no. 13, 2015) mainly concentrates on the US. This article brings the critical race (CR) literature on migrants' exclusion and oppression in the Netherlands to this debate. It discusses several essentialist shortcomings of this literature. First, CR authors do not contextualize "race" and racism, which repeatedly results in misreadings of the Dutch context. Second, their imposed totalizing notions of racism undermine the explanatory value of the concept. Third, the evidence for their claims remains inconclusive. Fourth, their contributions to the struggle against migrants' exclusion and oppression are limited. To avoid these shortcomings, I argue for a differentiation between "race"/racism and "ethnicity"/ethnicism as two separate concepts that need to be applied and understood in a non-essentialist way.